CHROMIUM AND COBALT LEVELS AMONG DENTAL TECHNICIANS IN THE NORTHERN JORDAN - Al-Hourani, Zeid; Al-Sarhani, Mansour; Al-Khatib, Ahed (European Scientific Journal, ESJ, 2013)
ï»¿Introduction: Dental technicians have higher occupational exposure to the heavy metals chromium and cobalt. Exposure to these metals is associated with many adverse health effects. Study objectives: To determine the prevalence of chromium and cobalt toxicity among dental technicians, and to correlate the occupational exposure for chromium and cobalt with occupational diseases. Methods and subjects: Study design and setting: Descriptive cross-sectional study design was utilized. The present study was conducted in the Northern Jordan. A total of 100 laboratory technicians were included in this study.,. These involved dental laboratory technicians (n=50) as sample group, and medical laboratory technicians (n=50) as a control group. Data was collected by a prepared questionnaire composed of both demographical and occupational variables. Blood samples were collected from the participants and were analysed for concentrations of cobalt and chromium at Princess Haya Center for Biotechnology using atomic absorption spectrometry technique. Results: The mean concentration of chromium was 46.18+58.20Î¼g/dL for dental technicians and 17.84+43.46Î¼g/dL for medical technicians. There was a significant relationship in the chromium exposure among dental technicians compared with medical technicians (P < 0.05). The mean concentration for cobalt was 2.23 + 6.53 Î¼g/dL, while it was 0.2+0.38Î¼g/dL for medical technicians. The difference in cobalt concentrations between the sample and control group was statistically significant (P < 0.05). This study revealed that the prevalence of some diseases such as diabetes and epilepsy do not associate with the occupational environment (dental or medical technicians), while other diseases such as bronchitis and allergy were prevalent a in dental technicians. Conclusions: Ddental technicians have more blood concentrations of the heavy metals Cchromium and Ccobalt compared with medical technicians, which are attributed to the occupational exposure and environmental conditions in dental laboratories.